The Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition alternative model of personality disorder - Widiger, Thomas A; Hines, Alexandra (Personality disorders, 2022)
The fifth edition of the American Psychiatric Association's Diagnostic and Statistical Manual of Mental Disorders (DSM-5; American Psychiatric Association, 2013) includes within a section for emerging measures and models an alternative model of personality disorder (AMPD). This article provides a brief overview of its development, noting, in particular, issues and controversies. The article concludes with a discussion of and recommendations for further research in regard to 8 issues: (a) whether the DSM-5 AMPD offers any incremental validity over DSM-IV with respect to the validity or clinical utility; (b) development of the treatment implications for the AMPD components; (c) whether the DSM-5 AMPD level of personality functioning (LPF) is a unitary construct; (d) whether the LPF does in fact identify the core of personality disorder, (e) whether the LPF is even necessary; (f) whether the AMPD trait model is sufficiently comprehensive in its coverage; (g) the synchronization of International Classification of Diseases, Eleventh Revision, and DSM-5 Section III; and (h) whether the future classification of personality disorder should continue to include any of the DSM-IV syndromes. (PsycInfo Database Record (c) 2022 APA, all rights reserved).The fifth edition of the American Psychiatric Association's Diagnostic and Statistical Manual of Mental Disorders (DSM-5; American Psychiatric Association, 2013) includes within a section for emerging measures and models an alternative model of personality disorder (AMPD). This article provides a brief overview of its development, noting, in particular, issues and controversies. The article concludes with a discussion of and recommendations for further research in regard to 8 issues: (a) whether the DSM-5 AMPD offers any incremental validity over DSM-IV with respect to the validity or clinical utility; (b) development of the treatment implications for the AMPD components; (c) whether the DSM-5 AMPD level of personality functioning (LPF) is a unitary construct; (d) whether the LPF does in fact identify the core of personality disorder, (e) whether the LPF is even necessary; (f) whether the AMPD trait model is sufficiently comprehensive in its coverage; (g) the synchronization of International Classification of Diseases, Eleventh Revision, and DSM-5 Section III; and (h) whether the future classification of personality disorder should continue to include any of the DSM-IV syndromes. (PsycInfo Database Record (c) 2022 APA, all rights reserved).